2019
DOI: 10.2166/aqua.2019.031
|View full text |Cite
|
Sign up to set email alerts
|

An experimental analysis on accuracy of customer water meters under various flow rates and water pressures

Abstract: Apparent losses are mainly due to metering errors in well-managed water supply systems. There are many types of water meters based on mechanisms to measure flow passing through. Therefore, selection of water meter type is important as meter type effects measurement accuracy. In this study, a total of 50 domestic water meters were tested under varying flow rates and different water pressures. Water consumptions of end-users show temporal changes depending on the life style of consumers. Flow rates passing throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The results revealed that the proposed method requires less computational time compared to the soccer league competition (SLC) algorithm. Karadirek [12] analyzed customer water meter accuracy under various water pressures and flow rates that might exist in the water distribution networks. The results revealed that water pressure has no effect on higher flow rates and causes customer water meter inaccuracies in lower flow rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results revealed that the proposed method requires less computational time compared to the soccer league competition (SLC) algorithm. Karadirek [12] analyzed customer water meter accuracy under various water pressures and flow rates that might exist in the water distribution networks. The results revealed that water pressure has no effect on higher flow rates and causes customer water meter inaccuracies in lower flow rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main challenge for using mechanical meters is to accurately measure individual water withdrawals. The accuracy is affected by many factors, including meter wear and tear, blockage of the meter inlet or strainer, depositions on the meter components, incorrect sizing, incorrect mounting position, the filling process of an empty pipe [4], generation of cavitation [5], and incorrect flow profile [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The main factor affecting the intake spectrum is the water consumption habits of the customers and it is the main unknown of all [18]. The flow rate that passes through a meter is the governing factor of the meter accuracy [7]. For a specific meter, its metering error would be different with different intake behaviors (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on muddy water pipeline irrigation mainly included the non-depositing critical velocity [10,11], solid-water mixture flow head losses [12] and anti-clogging technology [13]. The research on pipeline metering devices mainly includes the influence of water pressure [14], temperature [15,16], velocity distribution [16] and other factors on the metering device. Some researchers have also carried out theoretical analysis on one of the metering devices of muddy water pipelines [17,18].…”
Section: Introductionmentioning
confidence: 99%